ENT 530 Social Media Portfolio: Mira's Flowerpot Shop / Amirah Mokri - Mokri, Amirah (2021)
Mira's Flowerpot Shop is an online operating business that sells indoor plants and their accessories. This online business is a dropship under the owner of the local brand, Alfarifapotted. Mira's Flowerpot Shop operates on 2 platforms; Facebook and Whatsapp only. Customers can interact on any of the platforms provided. Both platforms are easy for customers to reach. Although Mira's Flowerpot Shop is a fully online business, our main location is in Bandar Baru Bangi, Selangor. Mira's Flowerpot Shop is also prepared to provide customers with an amazing and genuine online purchasing experience. We strive to provide only the best and highest-quality products to our customers at reasonable pricing. Furthermore, we place a high value on our customers' enjoyment and comfort. There are many plant options that can decorate a customer's home. As we are only a dropship business, the operating plan we use consists of promotion and advertising. We aspire to be a successful dropship business in Malaysia. To achieve this success, we will make improvements in this business over time to time according to the passage of time and the economy.